Sunitinib-Induced Hypothyroidism and Survival in Pancreatic Neuroendocrine Tumors - Mathew, Annie; Führer, Dagmar; Lahner, Harald (Hormone and Metabolic Research, 2021)
Sunitinib has been approved for the treatment of pancreatic neuroendocrine tumors, renal-cell carcinoma, and gastrointestinal stromal tumors. The elevation of thyroid-stimulating hormone serum levels is a common side effect. Studies suggest a correlation between sunitinib-induced hypothyroidism and treatment outcome in patients with renal-cell carcinoma and gastrointestinal stromal tumors. This study assessed whether sunitinib-induced hypothyroidism is a predictive marker of the objective response rate, progression-free survival, and overall survival in pancreatic neuroendocrine tumor patients. Twenty-nine patients treated with sunitinib for advanced pancreatic neuroendocrine tumors were included. The incidence of sunitinib-induced hypothyroidism was 33%. The median progression-free survival of patients who developed hypothyroidism was 16 months (95% confidence interval: 6.2–25.8 months) as compared with six months among euthyroid patients (95% confidence interval: 0.1–12.2 months) (p=0.02). The median overall survival was 77 months (95% confidence interval: 31.4–122.6 months) in hypothyroid patients but 12 months (95% confidence interval: 5.9–18.1 months) in subjects with euthyroidism (p=0.001). The median overall survival from the time of initial diagnosis ranged from 247 months in patients with hypothyroidism to 65 months in euthyroid subjects (p=0.015). Elevated thyroid-stimulating hormone levels are a prognostic biomarker of improved outcomes of sunitinib therapy in pancreatic neuroendocrine tumor patients.
Keywords: pancreatic neuroendocrine tumor; neuroendocrinology; predictive factor; tyrosine kinase inhibitor; survival